Relationship Between Demographic Factors and Consumer Buying Behaviour Towards Organic Cosmetic Products - Radhika, Vijay; Jain, Ruchi (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The recent years have experienced a massive shift in the global cosmetics industry as the demand of organic and natural cosmetic products rises. The increase in consumer awareness about the negative impact of synthetic chemicals in traditional cosmetics, as well as the increasing apprehension of environmental sustainability and the overall well-being of a person, has served as a factor in the growth of the organic cosmetic market. Organic cosmetic products are normally produced by use of natural ingredients that are of plant origin and have zero harmful chemicals like parabens, sulphates and artificial preservatives. Consequently, more consumers are turning to products that are more seen to be safe, environmentally friendly and products produced in an ethical manner. The aim of the present study is to discuss how the demographic factors are associated with consumer buying behaviour in relation to organic cosmetic products. They need to know how demographic factors like age, gender, income, education, occupation among others, affect consumer preferences in the organic cosmetic industry. Such demographic factors usually have a great influence on purchasing decisions, awareness, brand preference and readiness to spend on organic cosmetic products. The study is descriptive research design, and uses mainly primary data that is gathered using a structured questionnaire survey to consumers. A convenience sampling method was used to select a total sample of respondents and the data of the respondents were analysed with the help of statistical methods, including percentage analysis, cross-tabulation, and correlation methods to define patterns and relations between demographic factors and consumer buying behaviour. The study results suggest that demographics play an important role in consumer attitudes and buyer behaviour of organic cosmetic products. The consumers who have greater education and younger are more likely to be aware and prefer using organic cosmetic products. In the same manner, the level of income of consumers influences the readiness to buy high quality organic products in spite of the higher price. The differences by gender also arise in buying behaviors, whereby the female consumers tend to have higher interactions with the organic cosmetic brands. The research will offer important insights to cosmetic producers, marketers, and policy-makers who would want to learn the consumer preferences within the booming market in organic cosmetics. The findings indicate that demographic segmentation is crucial in creating effective marketing mix, product positioning, as well as awareness programs that will lead to sustainable and health-conscious consumption.